PENGEMBANGAN KREATIVITAS ANAK MELALUI PENGOLAHAN LIMBAH BOTOL PLASTIK BEKAS MENJADI BARANG FUNGSIONAL - Adi Ismanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Plastic waste has become a global problem and disrupts ecosystems, including in Indonesia which is the second ranked contributor. This condition requires a lot of collaboration from the government, private sector and also the role of the community to carry out the principles of 5R waste processing (recycle, reuse, reduce, replace and repair) in order to reduce environmental pollution from plastic waste. One of the efforts that will have a long-term effect is waste management education for early childhood to produce the character of the nation's successors who have awareness and concern for the environment, which can be done at the formal and informal education levels. Yayasan Rumah Pagi Bahagia is a cooperation partner of the Interior Design Study Program, Faculty of Art and Design, Tarumanagara University in various community service activities. Profile of PKM Partner